PEMANFAATAN EKSTRAK BUAH TAKOKAK (Solanum torvum Sw.) PADA FORMULASI MINUMAN SUPLEMEN SEBAGAI SUMBER ANTIOKSIDAN - Faisal, Hendri; Andry, Muhammad; Lumbantoruan, Jernih Marisatua (AGRIBIOS, 2024)
The takokak fruit (Solanum torvum Sw.) is a wild plant and a member of the nightshade family that thrives in fertile, water-rich soils. Takokak fruit (Solanum torvum Sw.) contains flavonoid compounds that act as antioxidants. Consuming beverages rich in antioxidants can enhance the immune system and inhibit the onset of degenerative diseases, one source of which can be found in supplement drinks containing takokak fruit extract. This study aims to determine the antioxidant activity value (IC50) in supplement drinks with takokak fruit extract using the DPPH method through UV-Vis spectrophotometry, and to identify the concentration of the supplement drink most preferred by volunteers with additions of 6%, 8%, and 10% extract. The research was conducted experimentally, including sample collection, plant identification, preparation of simplicia, extraction, characterization tests of simplicia, preparation of formulations, evaluation tests of formulations, and tests for free radical scavenging activity. The results showed that the IC50 values of the supplement drink formulations with takokak fruit extract were 120.9875 ppm for F1, 99.7778 ppm for F2, and 82.0887 ppm for F3. The beverage formulations exhibited a green color characteristic, with a solution pH of 6.32-6.37, and demonstrated good stability during storage using cycling tests. The takokak fruit extract can be formulated as a supplement drink source of antioxidants, classified as moderate and strong, with the concentration most preferred by volunteers being F1 (6%).